Integration of Technological Pedagogical and Content Knowledge in 21st Century Learning - Mohammad Ismail; Muhammad Zubair; Bagdawansyah Alqadri; Basariah Basariah (Postgraduate, University of Mataram, 2023)
This study aims to describe the implementation of technological pedagogical and content knowledge (TPACK) in learning in senior high schools. The research approach used is qualitative with descriptive type. Data was collected by conducting in-depth interviews and data analysis using analysis using the Miles and Huberman model with the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of TPACK in SMA has not been implemented optimally. This is because there are several obstacles encountered such as the unavailability of facilities that support optimally in several schools. The facilities in question include internet networks and learning tools in the form of computers and LCDs. In addition, the increase in the ability of teachers to implement TPACK-based learning is still uneven. This is a challenge in applying TPACK to learning optimally. The alternative chosen in learning is to use conventional learning by utilizing the facilities available at school.